Nanofibers as a drug carrier in ophthalmic therapy - Anna Czech; Ewelina Łyszczarz; Renata Jachowicz (Polish Pharmaceutical Society, 2021)
In ophthalmic therapy, drugs of various structures are used, administered into the conjunctival sac or onto the cornea. Novel concepts of technological development of the form of an ophthalmic drug delivery systems include obtaining a higher concentration of the drug in the target tissue of the cornea, while reducing side effects. In recent years, there has been a growing interest in using nanofibers as a dosage forms used in ophthalmic therapy. Nanofibers prepared by the electrospinning method are characterized by high porosity, high surface area/volume ratio and good mechanical properties. For their preparation, biocompatible and biodegradable polymers are used, such as: poly-ɛ-caprolactone, polymers and copolymers of lactic acid, chitosan, gelatin, collagen, polyvinyl alcohol, polyvinylpyrrolidone. They are considered as carriers of a drug substance in order to provide its prolonged or controlled release which is essential in the treatment of chronic diseases. The improvement in the bioavailability of fluocinolone acetonide was achieved after applying inserts containing nanofibers with poly-ɛ-caprolactone prepared using the electrospinning method to the rabbit eye. Poly-ɛ-caprolactone was also used to prepare nanofibers for intravitreal administration of dexamethasone acetate in retinal diseases to achieve controlled release of the drug substance. In order to reduce intraocular pressure in the treatment of glaucoma, contact lenses coated with timolol maleate nanofibers were used. The electrospinning method was also used to prepare nanofibers gelling in situ with gellan gum and pullulan polysaccharide. On the other hand, biodegradable core-shell nanofibers composed of monoclonal antibodies, bevacizumab, may be utilized as a new form of the drug for the ADM. Natural and synthetic polymers or their combinations are also used to prepare electospun nanofibers for the tissue engineering, e.g. in corneal tissues regeneration, for the preparation of cells for implantation or for direct injection of cells into the damaged area, e.g. retina, cornea.